Sistem Tanaman Pintar IoT - Norhanan, Norharis Muzammil; Ali, Zaurin; Azmi, Nurul Nasrin Nadhirah; Raymedin, Annis Farhana (Multidisciplinary Applied Research and Innovation, 2022)
Monitoring and watering systems on relatively small and medium scale industries are usually done manually by farmers with transporting buckets to the plants to be watered. Sometimes, they also use another method by using water pipes. But with doing that, they have to come to the plant site to open the pipes and close them back manually. Thus, to overcome these weaknesses, a system has been designed and constructed to combine the process of watering as well as monitoring the soil conditions using one way. If this project is not developed, farmers and entrepreneurs will face very serious problems because Malaysia is on the Equator line where the weather is dry and wet. The purpose of the innovation system is to help solve the problems that arise and indirectly produce a technology that is much needed to consumers such as farmers and also the entrepreneurs who have a desire to gardening. This is because, this system can monitor their plants, perform watering systems, and can also know the ambient temperature of the plants through their smartphones only. Besides, this project is produced using NodeMCU, soil moisture sensor, temperature sensor, LED, relay, and several other components that can complete this project to ensure every aspect can be seen and given full attention by the users. In conclusion, this IoT Smart Plant Watering System can help maintain plant freshness and help save operating cost.